Agustín Yáñez and Juan Rulfo: affinities and canonical contrasts - Sánchez, Pablo (Romanica Olomucensia, 2016)
This essay discusses one of the less-known aspects of the boom of the Latin American narrative: the construction of the novelistic canon of the second half of the 20th century. It takes as its starting point the case of two major Mexican narrators in the narrative after the Revolution, Agustín Yáñez and Juan Rulfo. The essay analyzes how and why fundamental Latin American critics of the boom valued the renewing capacity of both authors and assigned greater aesthetic importance to Rulfo, thus placing him in a central position of the canon that lingers to the present day.
Keywords: Agustín Yáñez; Juan Rulfo; boom of the Latin American novel; canon; Mexican fiction.